1982
DOI: 10.1590/s0034-89101982000500004
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de linhagens humana e silvestre de Schistosoma mansoni, na pré-amazônia: I - estudo em moluscos

Abstract: RESUMO:Foram isoladas na região da Baixada Maranhense (Brasil), linhagens humana (H) e silvestre(S) de Schistosoma mansoni a partir de miracídios eclodidos de ovos encontrados em fezes de doentes humanos autóc-tones da Região e de fígados de roedores silvestres naturalmente infectados. Biomphalaria glabrata, descentes de caramujos coletados no campo, foram expostos, isoladamente, aos miracídios H e S, mantidos isolados em moluscário e observados durante 100 dias. Moluscos normais foram mantidos nas mesmas cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
(4 reference statements)
0
3
0
3
Order By: Relevance
“…However, there have been only two reports where N. rattus (formerly named N. squamipes amazonicus) were found naturally infected (Bastos et al 1982(Bastos et al , 1984.…”
mentioning
confidence: 99%
“…However, there have been only two reports where N. rattus (formerly named N. squamipes amazonicus) were found naturally infected (Bastos et al 1982(Bastos et al , 1984.…”
mentioning
confidence: 99%
“…In the Maranhão state, more precisely in the Baixada Ocidental Maranhense, some rare and old studies also proposed to establish possible differences between these strains. According to Bastos et al (1982), when they verifi ed the virulence pattern of S and H strains (from Maranhão) in B. glabrata collected in the same area of occurrence of naturally infected rodents, it was observed that S strain was three times more virulent than H strain. For the authors, these data strongly suggest that there are suffi cient reasons to demonstrate that the two strains have some level of isolation in the nature, due to the existence of differences to the para sitological behavior in mollusks.…”
Section: The Wild and Human Strainmentioning
confidence: 99%
“…Studies of the participation of these rodents in schistosomiasis only mention N. squamipes, except for Bastos et al (1982Bastos et al ( , 1984, who reported naturally infected Nectomys squamipes amazonicus (currently Nectomys rattus (Pelzen (1883)). The water-rat Nectomys squamipes (Sigmodontinae) occurs in the Atlantic Forest, Rio São Francisco and Paraná Basins, and in small basins of Eastern Brazil below São Lourenço da Mata, Pernanbuco State, embracing the South, Southern and part of the Northeast regions (Fig.…”
Section: The Most Important Species Of Reservoir: Water-ratsmentioning
confidence: 99%